Grammatical Errors in English Informal Essays by The Sixth Semester of English Literature Students - Jumardin Muchtar (Hasanuddin University, 2021)
This research focused on Dulay's and Richard's theories about grammatical errors. This research purposed to (1) describe grammatical error types in English informal essay were made by the sixth semester of English Literature students in Makassar Islamic University and (2) find grammatical error causes in the informal essay were made by the sixth semester of English Literature students in Makassar Islamic University. The researcher used qualitative methods to analyse the types of error in students' questionnaires and essays based on Dulay's theory: omission, addition, misformation, and misordering. Meanwhile, the researcher also found error causes by Richard's theory, namely, interference, overgeneralization, ignorance of the rule restriction, incomplete rule restriction, and false concept hypothesized. This research demonstrated 210 errors in students' questionnaires and essays. First, fifty-two errors in omission: twenty-nine errors in the omission of the auxiliary verb, three errors in the omission of the ordinary verb, six errors omission of the noun, eight errors in the omission of a plural noun, two errors in the omission of gerund noun and four errors in the omission of the preposition. Second, ninety-three errors, in addition, those were: twelve errors in double marking, fifty-one errors in regularization, and thirty errors in simple addition. Third, fifty-one errors in misinformation last were fourteen errors in misordering, which were found in interference, overgeneralization, ignorance of the rule restriction, incomplete rule restriction, and false concept hypothesized. Keywords: Grammatical, Error, Informal Essays.